All Days 2010
DOI: 10.2118/130418-ms
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Service Lifetime of Coated Titanium Anodes

Abstract: Mixed metal oxide coated titanium anodes have been applied widely to cathodic protection as impressed current anodes in the oil/gas industry and for chlorine production in chlor-alkali industry. The anodic stability and service life are the main concerns in these applications. It has been known that oxide anodes have a very limited service life under operating conditions because of the severe corrosion of active component in the oxide mixture such as RuO 2 , leading to final deactivation of the anode.To increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This suggests that the addition of ruthenium oxide may prevent degradation and that RuOx electrode coatings may be suitable for chronic neural interfaces (Ullah and Omanovic, 2015). Additionally, prior studies of the electrochemical performance of ruthenium oxide electrodes have reported high charge storage capacities, high electrical conductivity, and a large electrochemically active surface areas [22,25,[33][34][35][36][37]. While these and our studies report promising results, future studies are necessary to determine the chronic reliability of implantable RuOx electrodes for recording and stimulation applications.…”
Section: Discussionmentioning
confidence: 53%
“…This suggests that the addition of ruthenium oxide may prevent degradation and that RuOx electrode coatings may be suitable for chronic neural interfaces (Ullah and Omanovic, 2015). Additionally, prior studies of the electrochemical performance of ruthenium oxide electrodes have reported high charge storage capacities, high electrical conductivity, and a large electrochemically active surface areas [22,25,[33][34][35][36][37]. While these and our studies report promising results, future studies are necessary to determine the chronic reliability of implantable RuOx electrodes for recording and stimulation applications.…”
Section: Discussionmentioning
confidence: 53%